Scanning Techniques for Nanobioconjugates of Carbon Nanotubes. (13th June 2018) - Umemura, Kazuo; Sato, Shizuma
Abstract : Nanobioconjugates using carbon nanotubes (CNTs) are attractive and promising hybrid materials. Various biological applications using the CNT nanobioconjugates, for example, drug delivery systems and nanobiosensors, have been proposed by many authors. Scanning techniques such as scanning electron microscopy (SEM) and scanning probe microscopy (SPM) have advantages to characterize the CNT nanobioconjugates under various conditions, for example, isolated conjugates, conjugates in thin films, and conjugates in living cells. In this review article, almost 300 papers are categorized based on types of CNT applications, and various scanning data are introduced to illuminate merits of scanning techniques.